Recontextualizing English Language Teaching through Local Wisdom in Islamic Higher Education: Insights from Lecturer Perspectives - Magfirah, Andi; Hasanah, Nurul; Hardiyanti, Hardiyanti; Pratiwi, Suci (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2026)
This study investigates the integration of local wisdom into English Language Teaching (ELT) within the context of Islamic higher education, highlighting its role in enhancing pedagogical quality and cultural relevance. In many ELT settings, instructional practices remain dominated by globalized content that often overlooks local cultural identity and religious values. This research adopts a qualitative design using a census sampling technique involving all 18 English lecturers at IAIN Parepare, Indonesia. Data were collected through semi-structured interviews conducted via digital platforms and direct interactions, and analyzed using thematic analysis, including coding, categorization, and interpretation. The findings indicate that lecturers perceive local wisdom as a valuable pedagogical approach that enhances student motivation, engagement, and comprehension by contextualizing learning through local cultural narratives and Islamic values. However, the integration of local wisdom is not yet fully optimized due to challenges such as limited curriculum support, insufficient institutional policies, lack of teaching resources, and resistance to pedagogical change. This study contributes to the development of culturally responsive pedagogy in ELT by demonstrating that integrating local wisdom can enrich learning experiences and strengthen students’ cultural and religious identity. It also offers practical implications for curriculum development, teacher training, and institutional policy reform in Islamic higher education.